2017
DOI: 10.1530/joe-17-0155
|View full text |Cite
|
Sign up to set email alerts
|

30 YEARS OF THE MINERALOCORTICOID RECEPTOR: Mineralocorticoid receptor null mice: informing cell-type-specific roles

Abstract: The mineralocorticoid receptor (MR) mediates the actions of two important adrenal corticosteroid hormones, aldosterone and cortisol. The cell signalling roles of the MR in vivo have expanded enormously since the cloning of human MR gene 30 years ago and the first MR gene knockout in mice nearly 20 years ago. Complete ablation of the MR revealed important roles postnatally for regulation of kidney epithelial functions, with MR-null mice dying 1-2 weeks postnatally from renal salt wasting and hyperkalaemia, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 66 publications
(76 reference statements)
0
27
0
Order By: Relevance
“…In the cardiovascular system, MR is expressed in cardiac myocytes, fibroblasts, endothelial cells, smooth muscle cells and immune cells (Lother et al 2015, DuPont & Jaffe 2017. A series of studies using cell type-specific MR deletion models revealed distinct roles of MR in these different cell types for hypertension, atherosclerosis, myocardial infarction and heart failure and in particular found MR in endothelial cells to be a crucial player in cardiovascular disease (Lother et al 2015, Young & Rickard 2015, Cole & Young 2017. Activation of MR in endothelial cells impairs vascular reactivity (Schafer et al 2013, Rickard et al 2014, Barrett Mueller et al 2015, promotes inflammation (Jia et al 2015 and contributes to cardiac fibrosis and hypertrophy (Jia et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, MR is expressed in cardiac myocytes, fibroblasts, endothelial cells, smooth muscle cells and immune cells (Lother et al 2015, DuPont & Jaffe 2017. A series of studies using cell type-specific MR deletion models revealed distinct roles of MR in these different cell types for hypertension, atherosclerosis, myocardial infarction and heart failure and in particular found MR in endothelial cells to be a crucial player in cardiovascular disease (Lother et al 2015, Young & Rickard 2015, Cole & Young 2017. Activation of MR in endothelial cells impairs vascular reactivity (Schafer et al 2013, Rickard et al 2014, Barrett Mueller et al 2015, promotes inflammation (Jia et al 2015 and contributes to cardiac fibrosis and hypertrophy (Jia et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Although these previous studies have clarified MR functions in the kidneys and cardiovascular tissues, the roles of MR in other epithelial tissues, such as the intestinal epithelium, have not been elucidated. MR is reportedly expressed throughout the intestine,22 and aldosterone increases the expression of the epithelial sodium channel (ENaC) in rats23; however, there are no studies focusing on the functions of MR in intestinal epithelial cells (IECs) using MR deletion mutants, the implementation of which is required 24. Furthermore, it is not clear how intestinal MR contributes to sodium dynamics and BP regulation.…”
mentioning
confidence: 99%
“…• Extra-adrenal production of aldosterone by aldosterone synthase within peripheral sensory neurons contributes to ongoing mechanical hypersensitivity via intrinsic activation of neuronal mineralocorticoid receptors • Intrathecally-applied aldosterone synthase inhibitor reduced aldosterone content in peripheral sensory neurons and subsequently attenuated enhanced mechanical hypersensitivity resulting from local inflammation A ldosterone is known to regulate the body's water and electrolyte balance through activation of corresponding mineralocorticoid receptors on epithelial cells of the renal cortical collecting ducts leading to sodium and water retention in exchange for excreted potassium. 1,2 Aldosterone is generated and secreted in the zona glomerulosa of the adrenal gland through local aldosterone synthase (CYP11B2). 1 Aldosterone circulates in the blood unbound (30 to 50% of total aldosterone) or bound to albumin-or corticosteroid-binding globulin (50 to 70% of total aldosterone).…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
“…1,2 Aldosterone is generated and secreted in the zona glomerulosa of the adrenal gland through local aldosterone synthase (CYP11B2). 1 Aldosterone circulates in the blood unbound (30 to 50% of total aldosterone) or bound to albumin-or corticosteroid-binding globulin (50 to 70% of total aldosterone). It is rapidly inactivated in the liver with a plasma half-life of 15 to 20 min.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%